Unexpected Behavior of the Heaviest Halogen Astatine in the Nucleophilic Substitution of Aryliodonium Salts. Issue 35 (15th June 2016) - Guérard, François; Lee, Yong‐Sok; Baidoo, Kwamena; Gestin, Jean‐François; Brechbiel, Martin W.
Abstract: Aryliodonium salts have become precursors of choice for the synthesis of 18 F‐labeled tracers for nuclear imaging. However, little is known on the reactivity of these compounds with heavy halides, that is, radioiodide and astatide, at the radiotracer scale. In the first comparative study of radiohalogenation of aryliodonium salts with 125 I − and 211 At −, initial experiments on a model compound highlight the higher reactivity of astatide compared to iodide, which could not be anticipated from the trends previously observed within the halogen series. Kinetic studies indicate a significant difference in activation energy ( E a =23.5 and 17.1 kcal mol −1 with 125 I − and 211 At −, respectively). Quantum chemical calculations suggest that astatination occurs via the monomeric form of an iodonium complex whereas iodination occurs via a heterodimeric iodonium intermediate. The good to excellent regioselectivity of halogenation and high yields achieved with diversely substituted aryliodonium salts indicate that this class of compounds is a promising alternative to the stannane chemistry currently used for heavy radiohalogen labeling of tracers in nuclear medicine. Abstract : Wherever I lay my At : Radiohalogenation of diaryiodonium salts has been investigated and a significantly higher reactivity of astatide has been observed. Regioselectivity and reaction kinetics can be controlled by varying the nature of substituents. The high reactivity of these precursors makes them an attractive alternative to the conventional arylstannane chemistry for radiolabeling with iodine and astatine.